2019
DOI: 10.1371/journal.pone.0216455
|View full text |Cite
|
Sign up to set email alerts
|

Association between the time spent watching television and the sociodemographic characteristics with the presence of overweight and obesity in Colombian adolescents (secondary analysis of the ENSIN 2010)

Abstract: Objective To determine the association between the time spent watching television and the sociodemographic characteristics with the presence of overweight and obesity in Colombian adolescents. Materials and methods Secondary analysis of the information obtained in the National Survey of the Nutritional Situation 2010 of Colombia, in a probabilistic sample of 18177 adolescents with an age range between 13 and 17 years. The time spent watching television and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 15 publications
1
16
0
1
Order By: Relevance
“…While it has been reported that BMI is one of the simplest and extensively used screening tool for child and adult obesity and it is not only used as an outcome measure for determining obesity but also as a useful anthropometric index for cardiovascular risk ( 30 ). Also, because of its simplicity, BMI is a standard tool to diagnose overweight/obesity as declared by WHO ( 6 , 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…While it has been reported that BMI is one of the simplest and extensively used screening tool for child and adult obesity and it is not only used as an outcome measure for determining obesity but also as a useful anthropometric index for cardiovascular risk ( 30 ). Also, because of its simplicity, BMI is a standard tool to diagnose overweight/obesity as declared by WHO ( 6 , 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…Internet addicted adolescents had also elevated risk of obesity in one study [19]. However, several other studies reported no signi cant association between obesity and screen time was observed [22,27,47]. The possible strong reason for this inconsistency, is the type of screen (e.g.…”
Section: Discussionmentioning
confidence: 90%
“…TV, video games or personal computer and so on) that is used in numerous studies. For nding the answer, we performed subgroup analysis; according to the results, those studies that de ned video games as their screen failed to reveal a positive association between screen time and obesity [23,47,58]. In the study by Franceschin MJ et al [16] adolescents with watching TV more than two hours per day had almost doubled chance of being obese compared with those who had less than 2 hours per day TV watching (OR = 1.73; 95%CI = 1.24-2.42) while the association was not signi cant for video game playing or PC use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous research that focused on the association between TV viewing and childhood overweight and obesity, the results were inconsistent. In some studies, a positive association was observed between long TV viewing time and childhood obesity [12–14] and in several studies, a dose-response effect between TV viewing time and childhood body mass index (BMI) was indicated [15, 16]. However, in other studies, an association between TV viewing time and childhood obese status was not observed [17, 18].…”
Section: Introductionmentioning
confidence: 99%